Defect-anchored confinement of Pt–In clusters via atomic layer deposition in hierarchical ZSM-5 for durable propane dehydrogenation - Jie Xu; Yi Yu; Chun Du; Yanfei Liu; Yaohui Dun; SenSen Yu; Fudong Liu; Yunsheng Dai; Rong Chen; Bin Shan (Chemical Engineering Journal, 2026)

The coarse-grained active layer as a thermal shield: Mechanisms of ice-debris complexes preservation at a retreating glacier margin in the Tianshan Mountains, China - Yu Zhou; Wenhai Shi; Guoyu Li; Wei Ma; Qingsong Du; Dun Chen; Junhao Chen (Cold Regions Science and Technology, 2026)

Fusarielins Q–Y: fusarielin polyketides from Fusarium asiaticum QA-6 inhabiting the roots of the cultivated Artemisia argyi and their antibacterial activity against aquatic pathogens - Xiao-Shan Shi; Sui-Qun Yang; Yu-Liang Dong; Xiao-Ming Li; Ling-Hong Meng; Yan-He Li; Dun-Jia Wang; Xing-Wang Zhou; Bin-Gui Wang (Phytochemistry, 2026)

Preparation, characterization, and similarity analysis of AJZU-1 martian soil simulant - Lin Sun; Bingkun Yu; Dun Wu; Guojun Cai (Engineering Geology, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

The performance and mechanism of sodium carboxymethyl cellulose in promoting the anaerobic ammonium oxidation coupled with Fe (III) reduction - Hong-Yan Meng; Shen Cui; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Pan Liang; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2026)

An adaptive auxiliary problem-based evolutionary algorithm for multi-objective optimization problems with complex constraints - Jun Ma; Yong Zhang; Dun-wei Gong; Yu Xue; Ali Wagdy Mohamed; Xiangjuan Yao (Swarm and Evolutionary Computation, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

Thawing permafrost under Qinghai-Xizang Highway and its impacts on road performance based on multi-source observed data - Guoyu Li; Mingtang Chai; Wei Ma; Fujun Niu; Dun Chen; Qingsong Du; Yu Zhou; Shunshun Qi; Yapeng Cao; Jianbing Chen; Liyun Tang; Yan Zhang (Cold Regions Science and Technology, 2026)

Direct preparation of a liquid bio-fertilizer from swine wastewater using ozone and earthworm-derived nitrogen-fixing bacteria to enhance nitrogen nutrition - JunJie Huang; PengFei Xie; XiaoYu Wang; XueYing Zai; Jing Yu; Min Song; GuangYing Weng; Miao Yu; XianYong Ma; Dun Deng (Journal of Water Process Engineering, 2026)

Effects of different iron compounds on the acclimation of Feammox sludge: Nitrogen-iron transformation, sludge physicochemical properties, and microbial communities - Pan Liang; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Hong-Yan Meng; Shen Cui; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Microbial life history strategies regulate soil organic carbon sequestration in response to thinning depending on microbial nutrient limitations - Wei Zhao; Wenli Zhu; Shuhan Yu; Fengjie Lian; Zihao Fan; Yuchen Liu; Peng Gao; Xingjian Dun; Zixu Zhang (Forest Ecology and Management, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Enhanced nitrogen removal in constructed wetlands by low-temperature tolerant heterotrophic nitrification bacteria Pseudomonas umsongensis YL-1: Pollutant removal, rhizosphere effects, and bacterial interactions - Wei Bian; Lei Yang; Yan-Li Li; Dun Guo; Hao-Qi Lu; Yu-Can Liu; Zhang-Wei He; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2025)

Promoting proliferation of Lactobacillus plantarum FN107 by Dendrobium oligosaccharide-mediated elimination of carbon catabolite repression - Dongchao Xie; Ruixue Zhang; Dun Si; Jiajun Huang; Lu Wang; Jinsong Zhao; Qiaoxian Yu; Jinping Si; Jingjing Liu; Peng Jin (Carbohydrate Polymers, 2025)

Changes of microbial life history strategies to soil nutrient limitations following vegetation restoration and its impact on carbon utilization efficiency - Wenli Zhu; Ming Hao; Wei Zhao; Shuhan Yu; Zihao Fan; Yuchen Liu; Xingjian Dun; Zixu Zhang; Peng Gao (Journal of Environmental Management, 2025)

IoT-enabled hierarchical thermoelectric nanocomposites for adaptive fire safety systems: Self-powered sensing and threshold-tunable alerts - Chuanshen Wang; Haorui Dun; Lu Liu; Hongliang Ding; Hongfei He; Bicheng Lin; Wenyu Hu; Na Sun; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2025)

Enhancing Feammox efficiency through riboflavin and humic acid: Nitrogen and iron transformation, energy metabolism, and microbial response - Dun Guo; Lei Yang; Hao-Qi Lu; Yu-Chao Wang; Hong-Yan Meng; Pan Liang; Shen Cui; Zhang-Wei He; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2025)

Integrating genome assembly, structural variation map construction and GWAS reveal the impact of SVs on agronomic traits of Brassica napus - Nian Wang; Xianshuai Song; Lieqiong Kuang; Ze Tian; Kaifeng Wang; Keqi Li; Lan Ge; Yu Wu; Xinfa Wang; Xiaoling Dun; Hanzhong Wang (Theoretical and Applied Genetics, 2025)

Source of dietary iron and zinc affects meat quality by altering muscular fatty acid profile, flavor substances, and metabolomics in finishing pigs - Zhimei Tian; Miao Yu; Yiyan Cui; Dun Deng; Min Song; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Meat Science, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

The synergistic influence mechanism of the alkali metal sodium and CO2 on coal rapid pyrolysis soot: Experiments and DFT calculations - Ziqi Zhao; Jirui Jin; Qian Du; Dun Li; Jianmin Gao; Heming Dong; Yu Zhang; Di Wu; Xiao Yang (Fuel, 2025)

Effects of dietary Brevibacillus laterosporus BL1 supplementation on meat quality, antioxidant capacity, and the profiles of muscle amino acids and fatty acids in finishing pigs - Guangying Weng; Miao Yu; Chenxi Deng; Yucheng Liu; Min Song; Jinping Deng; Yulong Yin; Xianyong Ma; Dun Deng (Meat Science, 2025)

Catalysts for sulfur: understanding the intricacies of enzymes orchestrating plant sulfur anabolism - Ziyue Xu; Dun Liu; Jiadong Zhu; Jiayi Zhao; Shenghai Shen; Yueduo Wang; Pei Yu (Planta, 2025)

BjuA03.BNT1 plays a positive role in resistance to clubroot disease in resynthesized Brassica juncea L. - Keqi Li; Kai Wang; Yiji Shi; Fenghao Liang; Xinru Li; Shunjun Bao; Balziya Maratkyzy Yesmagul; Maliha Fatima; Chengyu Yu; Aixia Xu; Xingguo Zhang; Sanxiong Fu; et al. (Plant Science, 2024)

Analysis of PANoptosis-related ceRNA network reveals lncRNA MIR17HG involved in osteogenic differentiation inhibition impaired by tumor necrosis factor-α - Jia-Xuan Li; Yu-Dun Qu; Chang-Liang Xia; Wei Zhang; Song-Song Wang; Shuan-Ji Ou; Yang Yang; Yong Qi; Chang-Peng Xu (Molecular Biology Reports, 2024)
Background Inflammatory cytokines such as Interleukin 1β(IL1β), IL6,Tumor Necrosis Factor-α (TNF-α) can inhibit osteoblast differentiation and induce osteoblast apoptosis. PANoptosis, a newly identified type of programmed cell death (PCD), may be influenced by long noncoding RNA (lncRNAs) which play important roles in regulating inflammation. However, the potential role of lncRNAs in inflammation and PANoptosis during osteogenic differentiation remains unclear. This study aimed to investigate the regulatory functions of lncRNAs in inflammation and apoptosis during osteogenic differentiation. Methods and results High-throughput sequencing was used to identify differentially expressed genes involved in osteoblast differentiation under inflammatory conditions. Two lncRNAs associated with inflammation and PANoptosis during osteogenic differentiation were identified from sequencing data and Gene Expression Omnibus (GEO) databases. Their functionalities were analyzed using diverse bioinformatics methodologies, resulting in the construction of the lncRNA-miRNA-mRNA network. Among these, lncRNA (MIR17HG) showed a high correlation with PANoptosis. Bibliometric methods were employed to collect literature data on PANoptosis, and its components were inferred. PCR and Western Blotting experiments confirmed that lncRNA MIR17HG is related to PANoptosis in osteoblasts during inflammation. Conclusions Our data suggest that TNF-α-induced inhibition of osteogenic differentiation and PANoptosis in MC3T3-E1 osteoblasts is associated with MIR17HG. These findings highlight the critical role of MIR17HG in the interplay between inflammation, PANoptosis, and osteogenic differentiation, suggesting potential therapeutic targets for conditions involving impaired bone formation and inflammatory responses.

Characterization of Tfgal-9: A galectin in innate immune system of Trachidermus fasciatus - Insights into its sequence analysis, expression patterns, and in vitro bioactivities - Ziyue Xu; Shanshan Yu; Chenjing Xu; Jiayi Zhao; Jiadong Zhu; Dun Liu; Min Peng; Yingying Liu; Qian Zhu (Fish & Shellfish Immunology, 2024)

Crystal orientation control in angstrom-scale channel membranes for significantly enhanced blue energy harvesting - Chia-Hui Chuang; Yu-Hsiang Peng; Chung-Kai Chang; Po-Ya Chang; Dun-Yen Kang; Li-Hsien Yeh (Chemical Engineering Journal, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Higher rice productivity and lower paddy nitrogen loss with optimized irrigation and fertilization practices in a rice-upland system - Weike Tao; Jiaqi Li; Weiwei Li; Chongxi Wen; Shen Gao; Yuhui Wang; Dun Liu; Lei Xu; Yu Jiang; Zhenghui Liu; Yanfeng Ding; Ganghua Li (Agriculture, Ecosystems & Environment, 2024)

Absorption and translocation of selected pharmaceuticals in Pistia stratiotes: Spatial distribution analysis using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Jiaxi Wang; Yiwen Zhu; Beibei Ye; Junling Dun; Xia Yu; Qian Sui (Journal of Hazardous Materials, 2024)

Magnolol-driven microbiota modulation elicits changes in tryptophan metabolism resulting in reduced skatole formation in pigs - Yuanfei Li; Yanchen Liu; Chunlong Mu; Changyi Zhang; Miao Yu; Zhimei Tian; Dun Deng; Xianyong Ma (Journal of Hazardous Materials, 2024)

The soil microbial necromass carbon and the carbon pool stability drive a stronge priming effect following vegetation restoration - Ming Hao; Guifang Wang; Qinghui Yu; Yuan He; Zixu Zhang; Xingjian Dun; Peng Gao (Journal of Environmental Management, 2024)

Understanding the release, migration, and risk of heavy metals in coal gangue: An approach by combining experimental and computational investigations - Jihong Dong; Jiabang Li; Yu Huang; Jingyu Zhong; Kai Dun; Min Wu; Lijuan Zhang; Quan Chen; Bo Pan (Journal of Hazardous Materials, 2024)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Dual-path activation of peroxymonosulfate by S vacancies in Mo/Fe-S for antibacterial applications - Jin Wang; Wenyu Ren; Yi Wang; Dun Zhang; Yu Wang; Peng Ju; Kunpeng Dou (Chemical Engineering Journal, 2023)

Identification, quantitative and bioactivity analyses of aroma and alcohol-soluble components in flowers of Gardenia jasminoides and its variety during different drying processes - Run Yu; Yue Li; Dun Si; Shulei Yan; Jingjing Liu; Jinping Si; Xinfeng Zhang (Food Chemistry, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

The effect of thinning intensity on the soil carbon pool mediated by soil microbial communities and necromass carbon in coastal zone protected forests - Zixu Zhang; Ming Hao; Qinghui Yu; Xingjian Dun; Jingwei Xu; Peng Gao (Science of The Total Environment, 2023)

Supramolecular nanoassemblies-mediated GSH depletion boosts synergistic chemo- and photodynamic therapy for immunogenicity enhancement - Dun Wang; Wei Ma; Yun Huang; Wei Wang; Shuang Li; Hongbin Liu; Yuqi Zhao; Dongdong Peng; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2023)

Bioactive compounds from Polygonatum genus as anti-diabetic agents with future perspectives - Yan Shi; Dun Si; Donghong Chen; Xinfeng Zhang; Zhigang Han; Qiang Yu; Jingjing Liu; Jinping Si (Food Chemistry, 2023)

Spiribacter salilacus sp. nov., a novel moderately halophilic bacterium isolated from a saline lake in China - Tong-Tong Zhang; Dun Liu; Xiao-Yu Zhang; Jia-Cheng Wang; Zong-Jun Du (Archives of Microbiology, 2023)

Short-term exposure to air pollution and outpatient visits for conjunctivitis: a time-series analysis in Urumqi, China - Si-Yu Gui; Xin-Chen Wang; Jian-Chao Qiao; Dun-Cheng Xiao; Cheng-Yang Hu; Fang-Biao Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Solid-state fermentation improves the quality of chrysanthemum waste as an alternative feed ingredient - Yiyan Cui; Su Peng; Dun Deng; Miao Yu; Zhimei Tian; Min Song; Jingjing Luo; Xinyan Ma; Xianyong Ma (Journal of Environmental Management, 2023)

Hydrochemical Evolution and Nitrogen Behaviors in Coastal Groundwater Suffered From Seawater Intrusion and Anthropogenic Inputs - Yu Dun; Junhong Ling; Rui Wang; Jun Wei; Qianyi Zhou; Yingjie Cao; Yizhang Zhang; Yingxue Xuan (Frontiers in Marine Science, 2022)
Coastal aquifers play key roles in providing freshwater resources to maintain the social and economic development in coastal areas. However, climate change and human activities have dramatically affected the quantities and qualities of groundwater in coastal aquifers. In this study, stoichiometric analysis of hydrogeochemistry, multivariate analysis, and isotopic trancing techniques were used to reveal the local hydrochemistry characteristics, the natural and anthropogenic origins, and the major hydrochemical evolution in a typical coastal aquifer located in the Pearl River estuary. According to hydrogeological conditions and groundwater burial conditions, the aquifer was divided into three zones, namely, semiconfined fissure groundwater (SFGW), recharged fissure groundwater (RFGW), and porous medium groundwater (PGW). Seawater intrusion, ion exchange, water–rock reaction, and human activities were the main controlling factors affecting the characteristics of groundwater, but there were significant differences in the main controlling effects of different zones. Among them, the samples from the SFGW was severely affected by seawater intrusion, and the contributions of seawater ranged from 6% to 97%. Obvious cation exchange process occurred during the seawater intrusion. The hydrochemical characteristics of the PGW and the RFGW were mainly controlled by water–rock interaction. In addition, human activities had further influence on the hydrochemical characteristics of groundwater, which resulted in elevated nitrate–nitrogen (NO 3 − –N). The mean NO 3 –N concentrations in the PGW and the SFGW were 6.58 and 3.07 mg/L, respectively. Furthermore, the δ 15 N–NO 3 − and δ 18 O–NO 3 − values in these two regions ranged from +2.35‰ to +27.54‰ and from +0.39‰ to +18.95‰, respectively, indicating that the anthropogenic input contributed to the increased nitrate. Redox analysis and dual nitrogen isotopic evidence indicated that denitrification was the predominant biogeochemical process in the PGW and the RFGW. This study highlights the impacts of seawater intrusion and anthropogenic inputs on hydrochemical evolution and nitrogen behaviors in coastal groundwater, which provides a scientific basis for the management of groundwater resources in coastal aquifers.

Freeze-thaw resistance of eco-material stabilized loess - Guo-yu Li; Xin Hou; Yu Zhou; Wei Ma; Yan-hu Mu; Dun Chen; Li-yun Tang (Journal of Mountain Science, 2021)

Development of 85 SNP markers for the endangered plant species Prunus mira (Rosaceae) based on restriction site-associated DNA sequencing (RAD-seq) - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Yu-e Bai (Conservation Genetics Resources, 2020)

Development and characterization of 72 SNP markers in Armeniaca sibirica based on transcriptomics - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Shulan Bai; Yu-e Bai (Conservation Genetics Resources, 2020)

Microbial communities present on mooring chain steels with different copper contents and corrosion rates - Jiajia Wu; Jieyan Gao; Dun Zhang; Faqi Tan; Jiang Yin; Yu Wang; Yan Sun; Ee Li (Journal of Oceanology and Limnology, 2020)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Zinc nutrition of wheat in response to application of phosphorus to a calcareous soil and an acid soil - Xiu-Xiu Chen; Wei Zhang; Qian Wang; Yu-Min Liu; Dun-Yi Liu; Chun-Qin Zou (Plant and Soil, 2019)

Nonlinear Rayleigh wave inversion based on the shuffled frog-leaping algorithm - Cheng-Yu Sun; Yan-Yan Wang; Dun-Shi Wu; Xiao-Jun Qin (Applied Geophysics, 2017)

Zinc uptake by roots and accumulation in maize plants as affected by phosphorus application and arbuscular mycorrhizal colonization - Wei Zhang; Xiu-Xiu Chen; Yu-Min Liu; Dun-Yi Liu; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

A regional-scale method of forecasting debris flow events based on water-soil coupling mechanism - Shao-jie Zhang; Fang-qiang Wei; Dun-long Liu; Hong-juan Yang; Yu-hong Jiang (Journal of Mountain Science, 2014)

Coal utilization in China: environmental impacts and human health - Jian Chen; Guijian Liu; Yu Kang; Bin Wu; Ruoyu Sun; Chuncai Zhou; Dun Wu (Environmental Geochemistry and Health, 2014)

Helicoverpa armigera nucleopolyhedrovirus orf81 is a late gene involved in budded virus production - Xiao-Feng Li; Huan Yu; Chuan-Xi Zhang; Hui Chen; Dun Wang (Archives of Virology, 2014)

Chelator-induced phytoextraction of zinc and copper by rice seedlings - Xiao-Zhang Yu; Dun-Qiu Wang; Xue-Hong Zhang (Ecotoxicology, 2014)

Homologous HAP5 subunit from Picea wilsonii improved tolerance to salt and decreased sensitivity to ABA in transformed Arabidopsis - Lingli Li; Yanli Yu; Jing Wei; Guixue Huang; Dun Zhang; Yong Liu; Lingyun Zhang (Planta, 2013)

Three-step continental-crust growth from subduction accretion and underplating, through intermediary differentiation, to granitoid production - Wei Liu; Xiao-Fei Pan; Dun-Yi Liu; Zhen-Yu Chen (International Journal of Earth Sciences, 2009)